2020
DOI: 10.1128/jvi.01193-20
|View full text |Cite
|
Sign up to set email alerts
|

Priming with DNA Expressing Trimeric HIV V1V2 Alters the Immune Hierarchy Favoring the Development of V2-Specific Antibodies in Rhesus Macaques

Abstract: The RV144 vaccine trial revealed a correlation between reduced risk of HIV infection and the level of non-neutralizing antibody (Ab) responses targeting specific epitopes in the second variable domain (V2) of the HIV gp120 envelope (Env) protein, suggesting this region as a target for vaccine development. To favor induction of V2-specific Abs, we developed a vaccine regimen that included priming with DNA expressing an HIV V1V2 trimeric scaffold immunogen followed by booster immunizations with a combination of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 103 publications
(177 reference statements)
1
7
0
Order By: Relevance
“…Expression of Spike DNA plasmids was analyzed upon transient transfection of HEK293T clone17 cells using the Calcium Phosphate DNA co-precipitation and DNA (1 microG DNA/ 60 mm plate) as described [32,63]. After 48 hours, supernatants and cells were harvested, and the cells were lysed in 1 ml of hypertonic N1 lysis buffer as described.…”
Section: In Vitro Analysis Of the Spike Dna Plasmidsmentioning
confidence: 99%
“…Expression of Spike DNA plasmids was analyzed upon transient transfection of HEK293T clone17 cells using the Calcium Phosphate DNA co-precipitation and DNA (1 microG DNA/ 60 mm plate) as described [32,63]. After 48 hours, supernatants and cells were harvested, and the cells were lysed in 1 ml of hypertonic N1 lysis buffer as described.…”
Section: In Vitro Analysis Of the Spike Dna Plasmidsmentioning
confidence: 99%
“…Expression of Spike DNA plasmids was analyzed upon transient transfection of HEK293T clone17 cells using the Calcium Phosphate DNA co-precipitation and DNA (1 microG DNA/60 mm plate) as described [32,63]. After 48 hours, supernatants and cells were harvested, and the cells were lysed in 1 ml of hypertonic N1 lysis buffer as described.…”
Section: In Vitro Analysis Of the Spike Dna Plasmidsmentioning
confidence: 99%
“…To this end, an uncleaved prefusion-optimized (UFO) gp140 Env trimer of CRF01_AE A244 with V3 truncation (UFO-BG.ΔV3) and A244 V1V2 on a trimeric 2J9C scaffold (V1V2-2J9C) were examined as uncomplexed proteins (UC) or in complex with mAb 2158 (IC) for immunogenicity in rabbits. A V1V2-2J9C DNA vaccine previously shown to promote the targeting of Ab responses to the V2 apex ( 27 ) was also incorporated for a co-immunization regimen. The data demonstrated that V1V2-specific Abs with distinct binding profiles were produced in the groups immunized with DNA and UFO-BG.ΔV3 UC or IC vaccines versus DNA and V1V2-2J9C UC and IC vaccines.…”
Section: Introductionmentioning
confidence: 99%